The Effect of Tax Avoidance on Company Value With Managerial Ownership as a Moderation Variable in Manufacturing Companies - Aisyah Amini; Azizul Kholis; Arfan Ikhsan (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to determine and analyze the effect of tax avoidance on company value, as well as analyze whether managerial ownership can be a moderation variable in the relationship of tax avoidance to company value in manufacturing companies on the Indonesia Stock Exchange (IDX). This research is a comparative casual research with a quantitative approach. The sample in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. The population in this study amounted to 228 companies. Sample selection using purposive sampling techniques and obtained samples from 32 companies with 5 years of observation so that 160 research data were obtained. The method of testing the hypothesis in this study uses a panel data regression model with a Fixed Effect Model approach and for testing moderation variables using a Moderated Regression Analysis (MRA) model. Data analysis of both models used version 12 of the Eviews program. The results showed that 1) tax avoidance has a positive and significant effect on company value, 2) managerial ownership is unable to moderate (weaken) the effect of tax avoidance on company value.